International Women’s Day 2019, Hilton Kuala Lumpur - UiTM, Faculty of Law (Faculty of Law, 2019)
In conjunction with the celebration of International Women’s Day 2019, Hilton Kuala Lumpur hosted the function on the 27 March 2019. Dr. Sheela Jayabalan and Dr. Normawati Hashim were invited as the guest speakers to talk on child management awareness. Both speakers shared their knowledge and insight on child bonding, understanding children especially in their teen years, education, challenges and sacrifices to achieve the goals of bringing up children. Being members of the Child Law Centre, Faculty of Law, UiTM Shah Alam, they also promoted the goals of the center and invited research collaborations from interested parties.